Effectiveness of immunomodulator listen in complex therapy of patients with multiresistant tuberculosis - Manana Sakhelashvili; Iryna Platonova; Hanna Shtybel (Academy of Sciences of Moldova, 2017)
47 patients were involved in the research. The use of immune response modifier glucosaminilmuramilpentapeptide (LIASTEN) along with the antimycobacterial therapy resulted in speeding up abacillation in (1.7±0.2) months, dispersion of focal abnormalities and infiltration in (1.5±0.1) months and the cicatrization of destruction cavities in (1.6±0.1) months as compared to the previous indicators. It should be noted that the average treatment duration during the intensive phase might be reduced by (1.9±0.3) months.